Lobbying and liquidity requirements: Large versus small banks - Shy, Oz; Stenbacka, Rune (Journal of financial stability, 2024)
We design a model with banks of unequal size operating subject to liquidity requirements in an imperfectly-competitive deposit market. We show that large banks have stronger incentives than small ones to lobby in order to relax the liquidity requirements unless they bear significantly higher lobbying costs. Therefore, lobbying magnifies asymmetries between banks. Furthermore, we establish that the organization of influence activities matters. An industry-wide bank association for lobbying to relax the liquidity requirements suffers from an internal conflict of interest and cannot simultaneously benefit both large and small banks if these have identical lobbying cost functions.